ZakaTech Strategy in Developing Inclusive Islamic Social Finance (ISF) in Indonesia - Muhammad Syah Budi (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Badan Amil Zakat Nasional (BAZNAS) as a sharia social financial institution offers the latest technology in the process of socialization, service and zakat fundraising. The new model offered is ZakaTech, an online payment model that makes it easier for a muzaki (zakat payer) to fulfill his or her responsibility to pay zakat in the midst of the covid-19 pandemic. In addition, the distribution of zakat funds using ZakaTech method is considered very effective in helping mustahik, especially helping the poor who are economically affected by the covid-19 pandemic. This paper aims to analyze the strategy of developing zakat model with Interpretative Structural Modeling (ISM) approach. The results show that the main strategy needed in terms of developing ZakaTech is the ability of human resources (amil zakat) in managing and analyzing data in the era of big data using digital services. The main elements involved in ZakaTech development in Indonesia include the government as a regulator, educational institutions (including universities), and existing industries (pentahelix).